A Study of Identity Crisis in Bravely Fought the Queen by Mahesh Dattani (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Bravely Fought the Queen is a play by Mahesh Dattaniwritten in1991 and it was published byPenguin Books in 2006. It deals“with the questions of gender, sexuality, identityand family politics simultaneously” (Rathee 31). Apart from these questions, the play explores altogether distinctive dynamics of the bravery of women such as endurance and resistance along the lines of search of identity. “Dattani represents unconventional, radical and rational dynamics of social issues, containing the seeds of the clash of the ‘self’ of the individual against the pre-determined schemes of society” (Agrawal 185).The dramatist focuses on the feminine concerns with the subservient theme of homosexuality in a society that authenticates only heterosexuality. People, who still feel uncomfortable talking about sex, cannot welcome these sexual variations such as homosexuality, bisexuality, and trans-sexuality. Majority of the people “love to talk about feminism because in a way that is accepted. But you can’t talk about gay issues because that’s not Indian. That doesn’t happen here” (Erin 21). Whereas, MaheshDattanihas stated that“being gay or lesbian is not right or wrong, it is reality and we have to learn to accept alternate relationships and live with them” (Qtd. in Erin 21). The motif of identity crisis has been discussed in the present research paper which is found here and there in the play without any endeavour.